Topographical Anatomy with autopsy guide and clinical notes - Valenta, Jiří (Karolinum, 2013)
This short synopsis of topographical anatomy is intended for medical students who already have a good knowledge of systematic anatomy. The chapters follow the arrangement usual in anatomy coursebooks, i. e. according to parts of the human body: head, neck, chest, pelvis, back and extremities. For a better understanding, the text is accompained by simplified drawings.
Keywords: Teoretické obory